The silver chair - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline (New York : HarperCollins, 1994)
Two English children undergo hair-raising adventures as they go on a search and rescue mission for the missing Prince Rilian, who is held captive in the underground kingdom of the Emerald Witch.
Christian Library Journal starred.
Kirkus Review.
5.7
5-8
Keywords: Adventure and adventurers -- Fiction; Fantasy; Narnia (Imaginary place) -- Fiction; Adventure fiction; Narnia (Imaginary place) -- Fiction; Fantastic fiction